2014
DOI: 10.3168/jds.2014-8196
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Homologous expression of recombinant and native thurincin H in an engineered natural producer

Abstract: The Bacillus bacteriocin thurincin H exhibits a wide inhibitory spectrum of activity against various foodborne pathogens, such as Listeria monocytogenes, and dairy spoilage bacteria, especially different Bacillus species commonly existing in dairy products. Previously, we constructed 3 plasmids to express native thurincin H homologously in an engineered natural producer, Bacillus thuringiensis SF361thnH(-). This host is deficient in thurincin H production because of an in-frame deletion of structural genes thn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Reported sactipeptides typically have a narrow spectrum of activity towards Gram-positive organisms, most notably Clostridium difficile, Listeria monocytogenes, and Bacillus cereus. 16,17,[46][47][48][49] Consistent with previously characterized sactipeptides, huazacin inhibited the growth of L. monocytogenes 4b F2365 with a minimum inhibitory concentration (MIC) of 4 μM (Table S4). These results with huazacin reinforce the concept that RODEO is a useful tool to accelerate RiPP discovery.…”
Section: Rodeo20-enabled Sactipeptide Discoverysupporting
confidence: 53%
“…Reported sactipeptides typically have a narrow spectrum of activity towards Gram-positive organisms, most notably Clostridium difficile, Listeria monocytogenes, and Bacillus cereus. 16,17,[46][47][48][49] Consistent with previously characterized sactipeptides, huazacin inhibited the growth of L. monocytogenes 4b F2365 with a minimum inhibitory concentration (MIC) of 4 μM (Table S4). These results with huazacin reinforce the concept that RODEO is a useful tool to accelerate RiPP discovery.…”
Section: Rodeo20-enabled Sactipeptide Discoverysupporting
confidence: 53%
“…In addition, subtilosin A also exhibited spermicidal activity (Silkin et al, 2008 ; Sutyak et al, 2008 ). Thurincin H produced by B. thuringiensis SF361 is effective against Bacillus spp., Micrococcus spp., Listeria spp, such as L. monocytogenes which are the main pathogens of human listeriosis (Lee et al, 2009 ; Sit et al, 2011b ; Wang et al, 2014c ). Simultaneously, thurincin H can be used as a food preservative for the control of food originated Gram-positive bacteria that cause the deterioration of sunflower honey (Lee et al, 2008 , 2009 ).…”
Section: Activity and Antibacterial Mechanism Of Sactipeptidesmentioning
confidence: 99%
“…With the advancement of bioinformatics methods and genomic sequencing technology, more and more sactipeptides have been discovered and identified in recent years. In 2014, Hertweck et al utilized anti-SMASH (Lee et al, 2008 ; Wang et al, 2014c ; Lee and Lee, 2016 ), BAGEL3 (Wang et al, 2014b ), BLAST and other bioinformatics tools to perform RiPPs genome mining on anaerobic bacteria with known genome sequences. The results demonstrated that 59 of 211 strains (28%) contain the RiPPs gene cluster.…”
Section: Distributions Of Sactipeptidesmentioning
confidence: 99%